Electrochemical Degradation and Cyclic Voltammetric Studies of Textile Reactive Azo Dye Cibacron Navy WB - Kariyajjanavar,P. (2010)
The removal of pollutants from effluents by electrochemical degradation has become an attractive method in recent years. This paper deals with the removal of reactive textile dye Cibacron Navy W-B (CNWB) from an aqueous medium by the electrochemical method using graphite carbon electrodes. Electrochemical behavior of reactive azo dye CNWB was performed with cyclic voltammetry in sulphuric acid medium using glassy carbon as working electrode. The potential range selected for the dye was in the range +700 mV to -450 mV. The voltammetric curve of CNWB shows cathodic peaks at +50 mV, -155 mV and -317 mV and anodic peaks at +382 mV and +547 mV, respectively. The decolourisation efficiency was assessed through UV-Visible studies. The LC-MS of the dye were analyzed before and after electrochemical treatment and confirmed that the azo groups and aromatic rings were destroyed. The effect of pH and nature of supporting electrolytes on the electrochemical degradation of dye was also studied. The maximum Chemical Oxygen Demand (COD) removal efficiency was ~100% for the dye solutions at 5 gL-1 of NaCl concentration. The results revealed the suitability of the present process for the effective degradation of dye effluents.